2016
DOI: 10.1159/000445063
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomographic Analysis of Retina in Retinitis Pigmentosa Patients

Abstract: Retinitis pigmentosa (RP) is a progressive inherited retinal disease characterized by nyctalopia, visual field constriction, and reduced full-field electroretinograms. The progressive loss of photoreceptors leads to vision loss at the end stage of RP. The prevalence of RP is approximately 1/4,000. Since it is one of the major causes of visual impairment worldwide, morphological and functional assessments are useful for estimating the retinal structure and function in RP. Optical coherence tomography (OCT) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 82 publications
3
53
0
1
Order By: Relevance
“…51 Several retinal modifications, including cellular hypertrophy, hyperplasia, neuronal migration, and network rewiring, have been previously described within the inner retina of RP patients. 52 Several studies have previously reported similar results of EZ disruption and thinning of ONL, [53][54][55] as well as thickening of inner retinal layers. 56,57 Microvascular attenuation was observed on OCT angiograms of RP patients at the perifoveal regions of the DCP and ICP.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…51 Several retinal modifications, including cellular hypertrophy, hyperplasia, neuronal migration, and network rewiring, have been previously described within the inner retina of RP patients. 52 Several studies have previously reported similar results of EZ disruption and thinning of ONL, [53][54][55] as well as thickening of inner retinal layers. 56,57 Microvascular attenuation was observed on OCT angiograms of RP patients at the perifoveal regions of the DCP and ICP.…”
Section: Discussionmentioning
confidence: 56%
“…50 These findings agree with our structural OCT results of EZ defects and decreased outer retinal thickness, especially in the more peripheral regions. [51][52][53][54][55] Patients with CME showed more outer retinal degeneration than RP patients without history of CME, which could indicate that presence of CME might be associated with more advanced forms of RP. However, the history of CME did not correlate with the severity of the disease as measured by visual fields.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of ERM formation remains unclear. However, it may include (1) idiopathic preretinal glial cell proliferation, (2) in ammation revealed by elevated aqueous are, and (3) chronic macular-vitreous traction [15][16][17]. Our results demonstrated that CME was the second most common macular abnormality, and this coincided with results from an Italian population for which Testa et al investigated macular abnormalities in 581 RP subjects [1] and found that the most frequent abnormalities was CME (20.4% eyes), followed by ERM (15.6%), VMT (5%), and MH (2%).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of CME in RP remains unclear; however, it may include (1) the breakdown of the blood-retinal barrier secondary to the degeneration of RPE and/or Müller cells, (2) anti-retinal antibodies, and (3) traction from ERM and VMT. There is no consensus on the relationship between CME and visual acuity in RP patients [15][16]. Sandberg et al believed that retinal thinning and thickening appeared to be associated with lower visual acuity in RP patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of high-resolution spectral domain-optical coherence tomography (SD-OCT), the morphological characteristics of RP have been elucidated well [2]. The most accepted primary structural characteristics of RP on SD-OCT include a thinner outer nuclear layer [3], a shorter photoreceptor layer [4, 5], reduced macular thickness [6] and volume [7], and a thinner choroid [8-11].…”
Section: Introductionmentioning
confidence: 99%